BIS and BAS Sensitivities at Different Levels of Personality Description: A Latent-Variable Approach with Self- and Informant-Ratings. Issue 2 (4th March 2021) - Vecchione, Michele; Ghezzi, Valerio; Alessandri, Guido; Dentale, Francesco; Corr, Philip J.
Abstract: We examine the structural overlap of the Behavioral Inhibition System (BIS) and the Behavioral Approach System (BAS) with Stability and Plasticity, the two higher-order factors encompassing the Big Five. Carver and White's BIS/BAS and the Big Five Inventory were administered to a sample of 330 adults, serving both as targets and informants. Self- and other-ratings were modeled by using the Correlated Trait-Correlated Method model. BIS and BAS correlated highly with metatraits, after method variance and measurement error were partialled out: BIS was positively related to Stability, while BAS was positively related to Plasticity and negatively related to Stability. After the higher-order factors were controlled, the BIS was highly and positively related to Emotional stability, whereas the BAS had a small but significant relationship with Extraversion. Findings are discussed with regard to the most appropriate level of generality/specificity at which the personality correlates of BIS and BAS can be investigated.